Modelo híbrido na educação superior: os desafios da inovação em uma realidade pós-pandemia de Covid-19 - Iwata Neto, Tatsuo (2021)
This thesis aims to provide an analytical and interpretive portrait of how students and teachers at a higher education school in São Paulo experienced the transposition of face to face classes to emergency remote education due to the requirement of social isolation due to the Covid-19 pandemic. More specifically, the objective was to find perspectives of a blended education in the set of speeches of these actors. It is a qualitative narrative research, which has been used in education studies for some time. Data were collected in two ways: students answered an online questionnaire; teachers were interviewed by Zoom. Through the content analysis proposed by Bardin (1977), the speeches were separated into categories and organized using the NVivo 11 Plus software. The idea was to capture the experience of the actors without creating a priori categories, as recommended by the actor-network theory. The interpretive exercise of these experience reports was carried out with the help of Ricoeur's proposal for a hermeneutic circle. The analysis and interpretation of the data resulted in the conception that, more than thinking about blended modalities, reflections on a blended future for education should start from the idea of flexibility, mobility and variety. Instead of thinking of the blended learning as a model in which online and in-person, synchronous and asynchronous activities or moments are mixed, a blended education should focus on student learning and protagonism, as well as taking into account the learning contexts in which it operates